A second functional furin site in the SARS-CoV-2 spike protein. Issue 1 (31st December 2022) - Zhang, Yue; Zhang, Li; Wu, Jiajing; Yu, Yuanling; Liu, Shuo; Li, Tao; Li, Qianqian; Ding, Ruxia; Wang, Haixin; Nie, Jianhui; Cui, Zhimin; Wang, Yulin; et al.
ABSTRACT: The ubiquitously-expressed proteolytic enzyme furin is closely related to the pathogenesis of SARS-CoV-2 and therefore represents a key target for antiviral therapy. Based on bioinformatic analysis and pseudovirus tests, we discovered a second functional furin site located in the spike protein. Furin still increased the infectivity of mutated SARS-CoV-2 pseudovirus in 293T-ACE2 cells when the canonical polybasic cleavage site (682–686) was deleted. However, K814A mutation eliminated the enhancing effect of furin on virus infection. Furin inhibitor prevented infection by 682–686-deleted SARS-CoV-2 in 293T-ACE2-furin cells, but not the K814A mutant. K814A mutation did not affect the activity of TMPRSS2 and cathepsin L but did impact the cleavage of S2 into S2′ and cell–cell fusion. Additionally, we showed that this functional furin site exists in RaTG13 from bat and PCoV-GD/GX from pangolin. Therefore, we discovered a new functional furin site that is pivotal in promoting SARS-CoV-2 infection.